2010
DOI: 10.1063/1.3386526
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene-multiwalled carbon nanotube complexes for bulk heterojunction photovoltaic cells

Abstract: We demonstrate the implementation of multiwalled carbon nanotubes-fullerene (MWNT-C60) complexes in bulk heterojunction organic photovoltaic (OPV) cells. Such a design takes advantage of the C60 as an electron acceptor, while the MWNTs serve as efficient charge transporters. Two types of chemically functionalized MWNTs were used to synthesize these complexes. The first used carboxylated nanotubes (c-MWNT), while the latter were functionalized with octadecylamine (o-MWNT). All the photovoltaic parameters were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…13 The difficulties in utilization of CNT as electron acceptors with yet the need to replace fullerenes by more favourable network for electron transport have led to the suggestion of using CNT exclusively for charge transport in a 3-component system: CNT-fullerene-conjugated polymer. [14][15][16][17][18][19][20] It was suggested that by combining both low concentrations of fullerenes and CNT one may be able to still utilize fullerenes for efficient charge separation while CNT with their superior electron transport properties and their low percolation threshold would serve for setting high-mobility pathways for electron transport. While of great potential, the morphology of the combined three-component system is very hard to control due to the very strong interactions within both fullerene and CNT components.…”
Section: Introductionmentioning
confidence: 99%
“…13 The difficulties in utilization of CNT as electron acceptors with yet the need to replace fullerenes by more favourable network for electron transport have led to the suggestion of using CNT exclusively for charge transport in a 3-component system: CNT-fullerene-conjugated polymer. [14][15][16][17][18][19][20] It was suggested that by combining both low concentrations of fullerenes and CNT one may be able to still utilize fullerenes for efficient charge separation while CNT with their superior electron transport properties and their low percolation threshold would serve for setting high-mobility pathways for electron transport. While of great potential, the morphology of the combined three-component system is very hard to control due to the very strong interactions within both fullerene and CNT components.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a cell with only C 60 as an acceptor (0.47 %), a 2.5-fold increase of PCE (1.22 %, Fig. 14B, Table 1) was obtained for the device using the graphene-C 60 hybrid material as an electron acceptor, which is higher than many high-performance PSCs with non-fullerene electron acceptors, such as functionalized graphene (1.1 %) [66] and C 60 -multiwalled carbon nanotube complex (0.80 %) [69]. Such enhancement in the PCE of the devices with the graphene-C 60 hybrid acceptor is mainly due to the improvement of the electron transport properties, since the incorporation of the graphene-C 60 hybrid into the active layer of the device could lead to the formation of more efficient electron transport pathway through percolation of the highly conducting two-dimensional graphene sheets.…”
Section: Graphene-based Materials As Active Layersmentioning
confidence: 93%
“…The addition of CNTs to organic photovoltaic (OPV) cells is of great interest due to the inherent properties of the tubes (Li et al, 2010). Organic solar cells have garnered a lot of interest since the discovery of dye sensitized solar cells, and have been envisioned as a cheaper alternative to silicon based cells.…”
Section: Photovoltaic Devicesmentioning
confidence: 99%